MASLD: insights on the role of folate in hepatic lipid metabolism - Yang, Minlan; Xiao, Xiaoyu; Mei, Jie; Pubu-ciren,; Gong, Quan (Frontiers in Nutrition, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is also known as fatty liver disease associated with non-alcoholic fatty liver disease (NAFLD), which is a spectrum of chronic liver diseases characterized by steatosis, inflammation, fibrosis and liver injury. The incidence and prevalence of MASLD is increasing rapidly worldwide. It is a multifactorial disease and there is no single drug approved for its treatment. The liver is the main organ that stores and metabolizes the B9 vitamin folate, which is synthesized mainly from dietary nutrients and intestinal microbiota and plays an important role in processes such as nucleic acid synthesis, methylation, and one-carbon metabolism (OCM). Serum folate levels are generally low in MASLD patients, and the low levels of endogenous folate lead to abnormalities in methionine metabolism and OCM, which disrupt lipid metabolism signaling pathways, and cause abnormalities in hepatic lipid metabolism, which may be related to the occurrence of metabolic disorders such as MASLD. Target folate may have beneficial effects in regulating hepatic lipid metabolism through regulating methionine metabolism, OCM and DNA methylation, and signaling pathways. Though a handful of studies argue that folate supplementation had no effect on blood pressure and lipids in patients with metabolic diseases, majority suggest that folate has the potential to serve as a potential therapeutic agent for the development of MASLD and the onset of metabolic associated steatohepatitis (MASH). To date, further research is needed in MASLD to (a) establish the dose of folate as a treatment, (b) determine the duration of therapy, especially in individuals with metabolic diseases, and (c) test its benefit on the different component features of MASLD (hepatic fat, inflammation, and fibrosis).